Cerebellar Continuous Theta Burst Stimulation for Aphasia Rehabilitation: Study Protocol for a Randomized Controlled Trial - Zheng, Kai; Chen, Mingyun; Shen, Ying; Xu, Xinlei; Gao, Fanglan; Huang, Guilan; Ji, Yingying; Su, Bin; Song, Da; Fang, Hui; Liu, Peng; Ren, Caili (Frontiers in Aging Neuroscience, 2022)
Background: Language recovery is limited in moderate to severe post-stroke aphasia patients. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising tool in improving language dysfunctions caused by post-stroke aphasia, but the treatment outcome is as yet mixed. Considerable evidence has demonstrated the essential involvement of the cerebellum in a variety of language functions, suggesting that it may be a potential stimulation target of TMS for the treatment of post-stroke aphasia. Theta burst stimulation (TBS) is a specific pattern of rTMS with shorter stimulation times and better therapeutic effects. The effect of continuous TBS (cTBS) on the cerebellum in aphasia patients with chronic stroke needs further exploration. Methods: In this randomised, sham-controlled clinical trial, patients (n=40) with chronic post-stroke aphasia received 10 sessions of real cTBS (n=20) or sham cTBS (n=20) over the right cerebellar Crus I + a 30-minute speech-language therapy. The Western Aphasia Battery (WAB) serves as the primary measure of the treatment outcome. The secondary outcome measures include the Boston Diagnostic Aphasia Examination, Boston Naming Test and speech acoustic parameters. Resting-state fMRI data were also obtained to examine treatment-induced changes in functional connectivity of the cerebro-cerebellar network. These outcome measures are assessed before, immediately after and 12 weeks after cerebellar cTBS intervention. Discussion: This protocol holds promise that cerebellar cTBS is a potential strategy to improve language functions in chronic post-stroke aphasia. The resting-state fMRI may explore the neural mechanism underlying aphasia rehabilitation with cerebellar cTBS.